An Alternative Approach to the Analysis of Taxation - Barzel, Yoram (Journal of Political Economy, 1976)
Because commodities as transacted are complex, tax statutes could not cover all margins subject to optimization. A tax will induce, then, substitution within the commodity away from the taxed attributes and into the others. The results of a test on cigarettes are consistent with our prediction that the effects of unit and ad valorem taxes will differ both from each other and from those predicted by the conventional model. It is shown that, although the market will adjust in numerous changeable characteristics, the adjustment is constrained by the condition that the sum of the dollar value of the inefficiencies and of tax paid is minimized.